Efeitos do marco regulatório do setor portuário instituído pela Lei n° 12.815 na atração de investimentos para a construção de instalações portuárias privadas - Glória, Igor Ribeiro da (2023)
The port infrastructure exploration sector is a market in which the state participates, providing the structure, making direct investments or exercising the regulation of activities carried out by private agents. In Brazil, until the enactment of Law No. 12.815, of 2013, the commercial exploitation of a port facility was authorized only to be carried out within the limits of public ports. However, since then, private agents has been allowed to build ports to mainly exploit it commercially, offering port services to anyone interested in moving cargo. This ammendent in the legislation aimed to attract private investment to the sector, thus contributing to reduce the existing port infrastructure deficit in the country. The present work evaluated the private investments carried out during the period from 2013 to 2022 in private port facilities, authorized by the public sector to expand or to be built after the new regulatory framework. We retrieve data from Antaq's administrative processes authorizing ng investment in port terminals, as well as information contained in reports from the regulatory agency and data published by the National Treasury. The results indicated that the authorized port facilities that were expanded or built were located especially in places where barriers to entry were lower, such as on the banks of inland waterways or, in the case of maritime facilities, where there was already the infrastructure to waterway access managed by some agent, such as the Port Authorities of organized ports. It was also verified that the authorized companies to construct port terminals with investments in excess of R$1 billion, updated to September/2021, have had difficulties in getting these projects off the ground, which could affect the sectoral planning of such infrastructure sector.